2020
DOI: 10.3892/etm.2020.8575
|View full text |Cite
|
Sign up to set email alerts
|

RIPK1 regulates the survival of human melanocytes upon endoplasmic reticulum stress

Abstract: Vitiligo is a common congenital or acquired disfiguring skin disorder. At present, endoplasmic reticulum (ER) stress has been identified to serve a critical role in the pathogenesis of vitiligo. Receptor-interacting serine/threonine-protein kinase 1 (RIPK1) is a protein serine/threonine kinase. The specific molecular mechanism of RIPK1 in human melanocytes upon ER stress remains to be determined. In the present study, RIPK1 was significantly downregulated in tunicamycin (TM)-induced ER stressed-human melanocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…S6 online), which undoubtedly leads to a dramatic phenotypic changes in TM-treated cells compared to mock-treated controls, one of the effects of TM conditioning we found was a reduction in the amounts of intracellular RIPK1, which correlated with sensitizing cells to NP-induced necrotic death. Although TM treatment did not appear to reduce the amount of intracellular RIPK1 in MEF cells 54 , recent studies using primary human melanocytes 55 and primary human melanocyte HEMn-MP cells 56 showed that TM treatment leads to a reduction of intracellular RIPK1, similar to finding in our system, when primary mouse BMDM were cultured on serumtreated glass slides. We further found that a necroptosis inhibitor GSK872, which was previously determined to function by blocking catalytic activity of RIPK3, was able to stabilize amounts of RIPK1 in TM-treated cells and protect cells from NP-induced necrotic death.…”
Section: Discussionsupporting
confidence: 85%
“…S6 online), which undoubtedly leads to a dramatic phenotypic changes in TM-treated cells compared to mock-treated controls, one of the effects of TM conditioning we found was a reduction in the amounts of intracellular RIPK1, which correlated with sensitizing cells to NP-induced necrotic death. Although TM treatment did not appear to reduce the amount of intracellular RIPK1 in MEF cells 54 , recent studies using primary human melanocytes 55 and primary human melanocyte HEMn-MP cells 56 showed that TM treatment leads to a reduction of intracellular RIPK1, similar to finding in our system, when primary mouse BMDM were cultured on serumtreated glass slides. We further found that a necroptosis inhibitor GSK872, which was previously determined to function by blocking catalytic activity of RIPK3, was able to stabilize amounts of RIPK1 in TM-treated cells and protect cells from NP-induced necrotic death.…”
Section: Discussionsupporting
confidence: 85%
“…Genetic factors contribute strongly to adult height, and certain genes linked with height [22] are involved in vitiligo-regulatory pathways. These include JNK (jun amino terminal kinase), PI3K (phosphatidylinositol 3 kinase), JAK1 (Janus kinase 1), CREB (cyclic AMP responsive element-binding) protein, ERK (extracellular signal-regulated kinase), and mTOR (mammalian target of rapamycin) [45][46][47][48]. JNK is involved in growth plate development and chondrocyte differentiation [49] and suppresses melanogenesis by interfering with CREB-regulated transcription coactivator 3-dependent microphthalmia-associated transcription factor (MITF) activation [50].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to XBP1, it was reported that receptor-interacting serine/threonine-protein kinase 1 (RIPK1), a protein serine/threonine kinase, could protect melanocytes from cell damage caused by ER stress by regulating the PI3K/AKT/mTOR and ER stress signaling pathways. 58 Therefore, more and more researchers have demonstrated the ER morphological and genetic abnormalities of melanocytes in vitiligo. Interestingly, ERS could not only induce melanocyte damage but also was reported to be associated with melanogenesis.…”
Section: The Link Between Abnormal Er and Melanocytes And Keratinocyt...mentioning
confidence: 99%